An Investigation into the Self-Concept of Inclusive High School Students with and Without Disabilities - Ali, Mokaddesh (Journal of Innovation in Education and Social Research, 2024)
Inclusive education is an important educational policy adopted by the Government of India. Students with disabilities (hearing, speaking, visual, cognition, motor skills, etc.) get less importance from peers, teachers, parents and others connected with the education system in and outside the schools. Children with disabilities have universally suffered from discrimination, violence and abuse, poverty, exclusion, and institutionalisation (International Save the Children Alliance 2001: 2). According to the World Bank Report (2007), 38% of the children with disabilities in the age group 6-13 years are outside the school education. This research was conducted to analyse the self-concept of the students with disabilities in the inclusive High Schools of Karbi Anglong district of Assam. The Self-concept Scale was administered to 12 students with disabilities and an equal number of students without disabilities. The results showed that students with disabilities in inclusive high schools have self-concepts of average and above average level, but there is a significant difference between the self-concepts of students with and without disabilities.